TRADISI DAN MAKNA FILOSOFIS KULINER MINANGKABAU - Waryono; Wirnelis Syarif (Jurnal Pendidikan dan Perhotelan (JPP), 2021)
The purpose of writing this article is to describe the traditions and philosophical meanings of Minangkabau culinary. The hope is that it will be useful as a reference for the younger generation of Minangkabau in choosing traditional foods to be served at traditional ceremonies and religious rituals. Library research was chosen as a method to achieve the goal by studying books, articles and websites related to Minangkabau culinary culture. The collected data was then analyzed using interactive analysis consisting of data collection, data presentation, data reduction and drawing conclusions. Minangkabau has a tradition of malamang and maantaan pabukoan which is still ongoing today. There are several routine ceremonial traditions that are always accompanied by various traditional culinary delights, such as lamang, nasi kunyik, nasi lamak, rendang, sambareh, pinyaram, lapek bugih, galamai. The meaning contained in the food served philosophically describes the existence of traditional leaders in Minangkabau, according to the deliberation and consensus of the previous ancestors, the bond of friendship and teaching sharing, patience, halal, thoroughness, a reflection of obedience and love.